Offenders’ perspectives on acquisitive crime targets and stolen goods disposal methods - Clare, Joseph (Journal of criminology, 2025)
This paper examines offenders’ perspectives about acquisitive crime targets and stolen goods markets in Australia that have not been comprehensively reviewed since 2005. Over the last 18 years there have been significant changes in the rates of property crime, reductions in cash usage, and rapid movements to online markets as a disposal outlet, that motivate this updated analysis. In late 2022, N = 107 detainees in a Western Australian police watchhouse were interviewed about their property offending frequency, offence preferences, target selection, disposal methods, and estimated financial return for targeted goods. Results demonstrated (a) meaningful shifts towards shoplifting and away from the other stealing offences, (b) increases in stealing for personal consumption rather than selling on, (c) declines in preferences for small electronic items, (d) ongoing dependence on drug dealers as a preferred outlet for off-loading stolen goods, (e) disposal of stolen goods is still quick, easy, and typically offenders receive about one-third of the original purchase price for items, and (f) growth in the use of online markets to dispose of stolen goods. The theoretical and applied implications of these findings are discussed, emphasising the importance of opportunity-focused interventions to prevent crime.